Primary vaginal squamous cell carcinoma arising in a squamous inclusion cyst: Case report - Němejcová, K; Dundr, P; Povýšil, C; Sláma, J (Ceskoslovenska patologie, 2012)
UNLABELLED: We report the case of a 39-year-old female with primary vaginal squamous cell carcinoma arising from a squamous inclusion cyst of the posterior wall. The tumor was located in the vaginal wall and extended into the rectovaginal septum. The overlying mucosa was intact. Histologically, there was invagination of the surface squamous vaginal epithelium forming a cystic lesion. In some areas of this invagination, the squamous epithelium showed dysplastic changes (VAIN3) transitioning into invasive squamous cell carcinoma. To the best of our knowledge, we have documented the first case of primary squamous cell carcinoma arising in a vaginal cyst in a patient without having undergone a previous hysterectomy. KEYWORDS: squamous cell carcinoma - vagina - squamous inclusion cyst - embryonal remnants - rectovaginal septum.
Keywords: nádory vaginy; Carcinoma in Situ; epidermální cysta; ženské pohlaví; spinocelulární karcinom; Humans; Epithelium; Carcinoma, Squamous Cell; Vaginal Neoplasms; Female; Cysts; karcinom in situ; cysty; epitel; lidé; Epidermal Cyst